Corporate Social Responsibility: Divesting From Apartheid - Listian Indriyani Achmad (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2022)
This study aims to emphasize the importance of companies’ Corporate Social Responsibility (CSR) in the fulfillment of their ethical responsibility to the international community with regards to human rights and to highlight the BDS (boycott, divestment, and sanctions) movement in its call for boycotting and divesting from companies operating in Occupied Palestine. The approach used in this study is a literature review of journal articles on CSR and BDS. This research found that in conducting their business, companies must have concern for humanity. Unethical actions by companies can be widely known by the public which can result in damage to companies’ reputations which in turn can lead to financial losses. Companies should not ignore the BDS movement. This paper only discusses boycotts of and divestment from companies in occupied Palestine, and earlier in South Africa. There have been limited studies about CSR implementation related to the BDS movement.